Modulations of corticospinal excitability following rapid ankle dorsiflexion in skill- and endurance-trained athletes - Hu, N.; Avela, J.; Kidgell, D. J.; Piirainen, J. M.; Walker, S. (European Journal of Applied Physiology, 2022)
Purpose Long-term sports training, such as skill and endurance training, leads to specific neuroplasticity. However, it remains unclear if muscle stretch-induced proprioceptive feedback influences corticospinal facilitation/inhibition differently between skill- and endurance-trained athletes. This study investigated modulation of corticospinal excitability following rapid ankle dorsiflexion between well-trained skill and endurance athletes.